Factors that affect the English language teaching-learning process in Ecuadorian public high schools - Cueva Miller, Wolegang Omar (2014)
The present research aims to identify and analyze the factors that affect the English language teaching-learning process in Ecuadorian public high schools. The general approach of the current work was quantitative. Surveys and note-taking techniques were considered as well as instruments such as observation formats and questionnaires were used to perform this study. To achieve the objectives of this research, five public high schools from Quito were selected. In each of these schools, three English teachers and three of their students were asked to participate in this research work. The results obtained revealed that numerous factors such as large classes, poor teaching resources, small classrooms and inadequate seating arrangement certainly affect the English language teaching-learning process. Besides this fact, inexperienced teachers, the excessive use of Spanish in classes and boring and repetitive tasks do not contribute to motivate students language acquisition.